Implementation of Amortization and Sinking Fund in Financial Literacy Education to Prevent Online Loan Traps Among Students of MAN 1 Bandarlampung - Indah Gumala Andirasdini; Fuji Lestari; Dila Tirta Julianty; Muklas Rivai (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community service initiative aims to strengthen students’ financial literacy by introducing key concepts such as amortization tables and sinking fund strategies. A significant proportion of students exhibit limited understanding of high-interest debt structures and lack essential personal financial management skills. The concept of amortization was introduced to demystify loan repayment mechanisms, while the sinking fund approach was presented as a disciplined strategy for long-term saving and financial goal achievement. Method: The program was implemented through a series of interactive socialization sessions, hands-on educational activities, and simulation workshops. Students actively developed amortization schedules and sinking fund models, enabling them to apply theoretical knowledge in practical contexts. To measure the impact, pre-test and post-test questionnaires were administered to assess improvements in students’ comprehension of financial principles. Practical Applications: The program successfully produced a range of accessible educational resources, including learning modules, student-friendly booklets, and digital Excel templates. These tools empower students to independently simulate loan repayment scenarios and savings plans, promoting self-reliance and informed financial decision-making. Conclusion: The results demonstrated a marked improvement in students’ financial literacy, with scores increasing from an average of 5.67 to 8.00. The integrated, experiential approach not only enhanced understanding but also fostered greater financial resilience among youth, equipping them with the knowledge to avoid predatory online lending practices that are increasingly common among students today.